Pengaruh Spiritual Branding, Consumer Protagonism Dan Integrated Marketing Communication Terhadap Keputusan Pembelian - Fitria Yuni Astuti; Gilang Kharisma Putra (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2023)
This study aims to examine the influence of spiritual branding, consumer protagonism, and integrated marketing communication in attracting consumer purchasing decisions muslim fashion shops were chosen as research objects because they sell religious clothes and knick-knack so that it is considered appropriate to be used as an object. Sampling using accidental sampling method, this method is a technique of determining sampling based on chance, that is, any consumer who meets the researcher by chance can be used as a sample. Obtained the number of sampling used in this study as many 203 respondent. Data were obtained by distributing questionnaires to consumers of muslim robes and clothing stores in kendal market directly to see respondents perceptions of spiritual branding, consumer protagonism, integrated marketing and purchasing decisions. The result showed that spiritual branding, consumers protagonism and integrated marketing communication statistically proved to have a positive and significant effect on consumer buying interest. The research result also prove that it simultaneously has a sig value of 0,000. The result indicate that the variables spiritual branding, consumer protagonism dan integrated marketing communication together are able to influence purchasing decision at the 1% level of confidence. In terms of R2 determination, the purchase decision variable can be explained by the spiritual branding, consumer protagonism and integrated marketing communication variable of 90,1% while the remaining 9,9% is explained by other variables not examined. Keywords : Spiritual Branding, Consumer Protagonism, Imc, Purchasing Decisions Abstrak Penelitian ini bertujuan menguji pengaruh consumer protagonism, spiritual branding dan integrated marketing communication dalam menarik keputusan pembelian konsumen Toko busana muslim dipilih menjadi objek penelitian karena menjual pakaian dan pernak-pernik yang religi sehingga dirasa tepat untuk dijadikan objek. Pengambilan sampel menggunakan metode Accidental sampling. Metode ini adalah teknik penentuan sampling berdasarkan kebetulan, yaitu siapa saja konsumen yang secara kebetulan bertemu dengan peneliti dapat digunakan sebagai sampel. didapatlah jumlah sampel yang digunakan dalam penelitian ini sebanyak 203 responden. Data diperoleh melalui pembagian kuesioner kepada konsumen toko gamis dan pakaian muslim di pasar kendal secara langsung untuk melihat persepsi responden mengenai spiritual branding, consumer protagonism, integrated marketing communication dan keputusan pembelian. Hasil penelitian menunjukan, secara statistik spiritual branding, consumer protagonism dan integrated marketing communication terbukti berpengaruh positif dan signifikan terhadap minat beli konsumen. Hasil penelitian juga membuktikan bahwa secara simultan memiliki nilai sig 0,000. Hasil tersebut menunjukkan bahwa variabel spiritual branding, consumer protagonism dan integrited marketing communication secara bersama-sama mampu mempengaruhi keputusan pembelian pada tingkat kepercayaan 1%. Secara determinasi R2, variabel keputusan pembelian dapat dijelaskan oleh variabel spiritual branding, consumer protagonism dan integrited marketing communication sebesar 90,1%. Sementara sisanya 9,9% dijelaskan oleh variabel lain yang tidak diteliti.Kata Kunci : Spiritual Branding, Consumer Protagonism, Imc, Keputusan Pembelian